PENGARUH KECERDASAN EMOSIONAL AUDITOR TERHADAP KINERJA AUDITOR PADA KANTOR INSPEKTORAT KABUPATEN WAKATOBI - Jumui, Jumui (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This study aims to determine the Effect of Auditor Emotional Intelligence on Auditor Performance at the Kendari City Inspectorate Office. Data collection was carried out using questionnaires. Data obtained from 24 People. Data analysis using multiple linear regression. The results of the analysis showed that emotional intelligence had a significant effect on the performance of auditors at the Kendari City Inspectorate Office, because the hypothesis proposed was previously accepted. This can be seen from the sig t value of 0.000, when compared to a significant level of 0.05 then the sig t value (0.000) < ? = 0.5 or 55 This can be interpreted that the research hypothesis (H 0) proposed is proven to be acceptable that there is a significant influence between the auditor's emotional intelligence variables on auditor performance at the Kendari City Inspectorate Office or in other words if rejected or H1 is accepted, so that a decision can be taken to reject H0 and H1 is accepted.